The process optimization of protopectin enzymolysis of vegetable raw materials for its use in ice cream production - Sapiga, Victoria; Mykhalevych, Artur; Osmak (Fedchenko), Tetiana; Polishchuk, Galyna (My University, 2021)
In foods, especially structured, an important role is played by the use of stabilizing substances, which include pectins. As protective colloids, they perform important technological functions - have a stabilizing and emulsifying ability, form a creamy consistency and increase overrun, which is important for the formation of ice cream quality indicators.
Keywords: protopectin; vegetable raw materials; ice cream; протопектин; рослинна сировина; морозиво; кафедра технології молока і молочних продуктів